Entrepreneurial Orientation, Technology Orientation, Contemporary Marketing and Small and Medium Enterprises (SMEs) Performance in Nigeria - Ibrahim, Maryam Imam; Abd Rani, Shamsul Huda; Ooi, Yeng Keat (2018)
Small and medium enterprises (SMEs) play a significant social and economic role in both developed and developing nations.Despite the relevance and important of the sector, the literature indicates there are very few studies that attempted to investigate the factors that influence the performance of SMEs in Nigeria, particularly the relationship between entrepreneurial orientation (EO), Technology orientation (TO), contemporary marketing (CM) and performance of SMEs.A cross-sectional design was adopted using questionnaire to collect data from 240 SME owner-managers in Nigeria.Questionnaires were distributed and collected through personally-administered method and Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the hypotheses.The findings of the study indicates a significant positive relationship between EO, TO and CM on the Performance of SMEs. The results offers important insights to regulators of SMEs, policy-makers, SMEs owner-managers, and researchers to further understand the effects of these strategic management variables.Owner-mangers of SMEs should accentuate on these variables to improve their performance.Policy-makers should support SMEs ownermanagers in the areas of training and capacity building.Lastly, limitations of the current study suggests opportunities for researchers interested in exploring other determinates of SMEs performance.